Effects of glucocorticoid-induced osteoporosis on bone tissue of rats with experimental periodontitis. (May 2017) - Sousa, Luzia Hermínia Teixeira; Moura, Eveline Valeriano; Queiroz, Ana Larissa; Val, Danielle; Chaves, Hellíada; Lisboa, Mario; Furlaneto, Flávia; Brito, Gerly Anne; Goes, Paula
Highlights: GIOP worsens ABL in animals subjected to EP. GIOP causes a greater decrease in osteoblast activity in animals subjected to EP. GIOP causes bone loss in femur of animals subjected to EP. Abstract: Objective: To evaluate the effects of osteoporosis induced by glucocorticoid (GIOP) on bone tissue of rats with experimental periodontitis (EP). Design: 48 male Wistar rats divided into groups: Naïve, EP, GIOP and GIOP + EP. Rats of GIOP and GIOP + EP groups received 7 mg/kg of dexamethasone intramuscularly once a week for 5 weeks. Following, EP and GIOP + EP groups were subjected to ligature-induced periodontitis. Naïve group experienced no manipulation. After 11 days, the animals were euthanized and left maxillae collected for macroscopic, radiographic, micro-tomographic and microscopic analysis of alveolar bone loss (ABL). Blood samples were collected for determination of bone-specific alkaline phosphatase (BALP) levels and the right femurs were removed for radiographic and biomechanical analysis. Results: EP caused ABL and reduced BALP levels (p < 0, 05), but it did not change the architecture or biomechanics of femur, compared to Naïve. GIOP did not cause ABL, but it significantly decreased alveolar bone mineral density (ABMD), bone percentage and trabecular thickness (Tb.Th) and increased alveolar bone porosity (p < 0.05) and significantly reduced BALP serum levels, as well as radiographic density and Young's module of femur, compared to Naïve. There was a greater ABL in group GIOP + EP when compared to EP (p < 0.05). GIOP + EP caused a greater decrease on ABMD, Tb.Th, bone percentage and increased bone porosity (p < 0.05) and also presented a significant reduction in BALP levels (p < 0.05), in radiographic density and in Young's module of femur compared to EP (p < 0.05). Conclusions: GIOP can potentiate the destructive effects of EP on alveolar bone and alter the systemic bone loss, by promoting bone resorption and reducing osteoblast activity.